2021
DOI: 10.1007/s43452-021-00188-5
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium alloyed tungsten borides synthesized by spark plasma sintering

Abstract: Tungsten borides (WBx; x = 2.5 or 4.5) with an increasing substitution of tungsten by zirconium from 0 to 24 at.% were synthesized by spark plasma sintering (SPS) for the first time. The influence of the holding time (2.5–30 min) on the densification behavior, microstructure evolution and development of the properties of W–Zr–B compounds were studied. The samples were characterized using scanning electron microscopy (SEM) for microstructure analysis, X-ray diffraction (XRD) for phase identification, Vickers mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…With an increasing zirconium content, the electrical conductivity of the SPSed specimens increased both in W 1−x Zr x B 4.5 and W 1−x Zr x B 4.5 (0 < x ≤ 0.24). W 0.76 Zr 0.24 B 2.5 sintered at a 24 min holding time is characterized by the highest electrical conductivity of 3.961 × 10 6 S/m, which is similar to the electrical conductivity of WC-Co cemented carbides [9]. In the case WB 4 alloyed with chromium (Cr), Mohammadi et al [13] showed that addition of 10 at.% Cr on a metals basis results in an increase in microhardness (at 0.49 N) from 43.3 ± 2.9 GPa for pure WB 4 to 53.5 ± 1.9 GPa and the defect structure of this material may be responsible for the hardening trends observed for the solid solutions.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…With an increasing zirconium content, the electrical conductivity of the SPSed specimens increased both in W 1−x Zr x B 4.5 and W 1−x Zr x B 4.5 (0 < x ≤ 0.24). W 0.76 Zr 0.24 B 2.5 sintered at a 24 min holding time is characterized by the highest electrical conductivity of 3.961 × 10 6 S/m, which is similar to the electrical conductivity of WC-Co cemented carbides [9]. In the case WB 4 alloyed with chromium (Cr), Mohammadi et al [13] showed that addition of 10 at.% Cr on a metals basis results in an increase in microhardness (at 0.49 N) from 43.3 ± 2.9 GPa for pure WB 4 to 53.5 ± 1.9 GPa and the defect structure of this material may be responsible for the hardening trends observed for the solid solutions.…”
Section: Introductionsupporting
confidence: 53%
“…It is clearly seen that the densification process is complete and after 24 min the displacement of punch is nearly constant. Optimal sintering parameters were selected on the basis of [9], where the influence of the holding time (2.5-30 min), sintering temperature and compacting pressure on the densification behavior, microstructure evolution and development of the properties of W-Zr-B compounds were studied. An example of sintering curves (chromium) is presented in Figure 1.…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
See 3 more Smart Citations